Nursing now and always: evidence for the implementation of the Nursing Now campaign - Isabel Amélia Costa Mendes; Carla Aparecida Arena Ventura; Manoel Carlos Neri da Silva; Valeria Lerch Lunardi; Ítalo Rodolfo Silva; Sara Soares dos Santos (Universidade de São Paulo, 2020)
Objective: to identify the guiding axes of the documents that grounded the Nursing Now campaign and relate the recommendations of these documents to the campaign goals. Method: documentary research, based on the analysis of the documents that promoted the Nursing Now campaign. The data were collected between March and April 2020, using a form structured into: background, scope, challenges and potentials of health/nursing professionals and recommendations for the future. Results: the challenges and the need for investments in the health and nursing workforce to achieve the Sustainable Development Goals were evidenced. The report of the High Level Commission on health Employment and Economic Growth presents important recommendations, also introduced in the Triple Impact Report and in the Strategic Directions for Nursing and Midwifery, converging to the goals of the Nursing Now campaign, stimulating a profile of nurses with technical, political and leadership skills, engaged in health policy-making, and the effectiveness of their practice is clear to the entire society. Conclusion: knowledge about the dynamics of the factors that converged to the development of the Nursing Now campaign may be a condition for achieving its goals. This reality reveals evidence that global health will not be ensured without strengthening Nursing first.